Bioinformatic pipeline for phenotype-genotype association analyses with limited genotypic data : Phytophthora infestans and its resistance to mefenoxam case study (2018)
"Here, we aimed to create a framework to facilitate the analysis of phenotypic and genotypic information collected from oomycete microorganisms. We have used Phytophthora infestans as a model organism to illustrate the potential of a custom pipeline for phenotype-genotype association analyses with limited genotypic data. To this end, we tested the sensitivity of P. infestans to mefenoxam during in vitro assays and attempted to find significant associations between the observed phenotypes and the genotypes of 12 microsatellite markers by combining bioinformatic tools currently available."-- Tomado del Formato de Documento de Grado.